If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + -6 = a Reorder the terms: -6 + w = a Solving -6 + w = a Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + w = 6 + a Combine like terms: -6 + 6 = 0 0 + w = 6 + a w = 6 + a Simplifying w = 6 + a
| 3(w-1)+3(w-2)=3 | | 6d-8=-2 | | (4x+5)(2x^2+7x+8)= | | n-12=-17 | | 2x-3/4x+9 | | 10*36/10=-36 | | 6x+y+4=-15+9y-x | | f(18)=4x-2 | | 2m=5/3m-1 | | -3(4x-2)=6 | | 14r+12=13r+14 | | 7/16+7/16+x+x=11/4 | | 27a+70-40-8= | | -5=19-3x+(-6) | | 6x+9-2x=29 | | 15x-7=80 | | 3(z+2)=5z+16 | | t+7=-13 | | y=4/11*15 | | 7/16+7/16+x+x=23/4 | | y=4/11x15 | | -4n-3+6n=-2 | | 200+1= | | (4x^3-5x^2+6x)+(3x^3+7x^2-11x)= | | 4a+2=2+8 | | -2-4=9.2 | | y=4/11x | | 7x+15=3#-5 | | -8=3m+5-4 | | 2451.12/56 | | -3x-3-4x=11 | | (4/9)^3 |